Confirming Human Antiquity: Spain and the Beginnings of Prehistoric Archaeology - Pelayo López, Francisco Luís; Gozalo Gutiérrez, Rodolfo (Complutum, 2013)
During his first visit to Spain in 1862, Louis Lartet together with Edouard de Verneuil and the Spanish mining engineer Casiano de Prado visited the San Isidro archeological site in Madrid. There they obtained a worked silex tool, which the former two then described and illustrated in the Bulletin de la Société Géologique de France. Three years later, Edouard Lartet together with Henry Christy and Hugh Falconer designed a project to extend the exploration in the field of prehistoric and archaeological works to the Iberian Peninsula. After Christy’s death at the beginning of 1865, and Edouard’s illness, it was Louis Lartet who undertook the research program of Prehistoric Archaeology South of the Pyrenees. He conducted excavations in caves in Álava and the Cameros Mountains (La Rioja region, Spain). At the same time as these excavations, an influential group of geologists was emerging in Spain who disseminated the findings, principles and practices of the new discipline.